Effect of synbiotics on caecal morphology and lesion score in broilers infected with Eimeria tenella - Surawat Chalorsuntisakul (2018)
The extensive use of the anti-coccidial drugs for prevention and control of coccidiosis in poultry has been a major factor in the success of the industry. The aim of this study was to investigate the influence of a synbiotic which combined between 106 cfuymL of Lactobacillus plantalum CMUFP002, and 2% Shallot extract vyv mix in water on Eimeria tenella infections in broiler chickens. One hundred and thirty-five day-old male broiler chicks were randomly assigned to three cages with three replications per treatment, with treatment groups including: (1) No synbiotic feeding to a non-infected, group; (2) no synbiotic feeding to chicks infected with 20,000 Eimeria tenella sporulated oocysts; and (3) synbiotic feeding to chicks infected with 20,000 Eimeria tenella sporulated oocysts. Lesion scores were assessed by gross pathological examination based on a scale of 0-4 at 0, 3, 6, 9, and 12 days post infection. Untreated broilers infected with E. tenella were found to have highly damaged caeca (P50:05) at days 6 and 12, whereas broilers infected with E. tenella but treated with the synbiotic also had damaged caeca, but with less damage than infected broilers fed no synbiotic. Broilers fed the synbiotic were also found to have altered epithelial morphology, but less so than the non-treated group. These results indicate that synbiotics may have a preventative effect on coccidiosis in broilers, but do not fully protect against the negative impact of the infection.